التقنيات والوسائل التعليمية فى تدريس مهارة الإستماع - Khoirun Nisa; Laili Ni’mah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Listening Skills (Maharah Istima ') are basic or primary skills in language learning, meaning they are lessons that must be taught the first time before other skills such as reading, writing and speaking skills. Or a skill that someone hears the first time from his mother or a skill that students learning a language must know, of course, to facilitate the achievement of these skills, appropriate techniques and media are needed to support it. Learning media is a medium, tool or material used by teachers to facilitate the teaching and learning process. In other words, instructional media is a tool for explaining intentions and thoughts, or training language skills, and generating other skills, without having a teacher use words, symbols and numerical statistics. Listening skills techniques require listening practice, for example by hearing sounds or analyzing sounds (Tahlil Ashwat), imitating and repeating them. So the practice of listening means trying to understand what is being heard. While the media in learning listening skills, for example, listening to sound from cassettes, CDs, lectures, language labs and television.